POTENTIAL EXTRACTS OF PANGIUM EDULE REINW AND DERRIS ELLIPTICA WALLICH AS BOTANICAL MOLLUSCICIDES FOR MANAGEMENT OF GOLDEN APPLE SNAIL Pomacea canaliculata Lamarck - Jacklin Stella Salome Manoppo (Universitas Sembilanbelas November Kolaka, 2017)
The research purposed was compared of two extracts as molluscicidal activities from root of Derris elliptica Wallich. and Pangium edule Reinw seed, that assessed to 3-month old snails Pomacea canaliculata L. The Golden apple snails is widely regarded as worst invasive pest species in the rice growing area. It normally destroys the young stems and leaves paddy and could consume 7 – 24 rice seedlings per day. The experiment research started with the mortality test of the golden apple snail, meanwhile hexane extract fraction and etanol extract fraction have completely jumble mode; using the lethal concentration (LC) have mean to describe short term potency of poisonous (toxicity) from materials and can gave little effect or impact for environment; processing phytochemical test from n-hexane extract and etanol extract of root D.elliptica and P.edule showed positive to contain tanin, saponin and fenol. The data of LC50 from n-hexane fraction measure with probit analyze (9,905 mg L-1) by D.elliptica L. with high toxic category, and n-hexane fraction (11,574 mg L-1) by P.edule Reinw. with toxic category are more effective for golden apple snail control. The golden apple snail mortality was highest using 5000 ppm n-hexane fraction showed 93,3% from D.elliptica and using 5000 ppm n-hexane fraction from P.edule showed 63,3%. In conclusion, both of extracts from D.elliptica roots and P.edule seeds was showed potency as botanical mollusicicides and it can be apply in the field